(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
This research is based on the phenomenon of the discovery of temple artifacts as cultural heritage, which are often found in the Yogyakarta region at a depth of approximately 2 to 7 meters from the surface, with the location of the discovery varying from rice fields, settlements, to areas that have been planned in the master plan for development. This condition causes problems in the form of incompleteness in the restoration process, due to limitations in space, resources, and connectivity with the surrounding area context. On the other hand, various countries have proven the success of the application of digital technology in supporting the preservation of cultural heritage, but in Indonesia, especially in the case of buried temples, its application is still limited. This study aims to reveal the role of digital technology, specifically virtual reality (VR) applications, in supporting cultural heritage preservation efforts in the case of buried temples in Yogyakarta. The research method uses a qualitative approach with an architectural case study, which combines literature review, field observation, and interpretive analysis of the potential use of VR and Heritage BIM integration in the context of preservation. The research results show that VR and HBIM technology play a significant role in presenting three-dimensional visual representations that are able to strengthen public understanding, education, and immersive experiences, so that the preservation of buried temple cultural heritage can be realized in a more meaningful, sustainable, and adaptive manner to the challenges of modern development.